Analisis Pendapatan Peternakan Sapi Potong Di Desa Rambung Susu Kelurahan Kerasaan I Kecamatan Pematang Bandar Kabupaten Simalungun - Feri Andrian; Nur Asmaq (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study was conducted in Rambung Susu Village, Simalungun Regency, North Sumatra, at the end of 2025, aiming to analyze the feasibility and income of beef cattle farming. The research method used was a descriptive quantitative approach, with data collected through observation and interviews using questionnaires. The sample was determined using purposive sampling with criteria including farmers having at least 3 years of experience, owning ≥5 cattle, and implementing an intensive management system. The data used consisted of primary and secondary data. The analysis was carried out by calculating total cost (TC), total revenue (TR), net income, and the business feasibility ratio (R/C). The results showed that the average total production cost was IDR 62,015,416.67, while the total revenue was IDR 78,566,666.67, resulting in a net income of IDR 16,551,250. The R/C Ratio value of 1.27 indicates that beef cattle farming is feasible and profitable, where every IDR 1 of cost generates IDR 1.27 in revenue. Thus, beef cattle farming in the study area has good economic prospects and strong potential for sustainable development to improve farmers’ welfare.